Análise semiótica das representações didáticas das placas tectônicas no ensino de geografia - Furlan, Thays Zigante (2018)
The difficulty in the representation of the geological contents occurs because of the comprehensive, dynamic and diversified character that these categories present as a synthesis of the endogenous and exogenous processes of the Earth. In order to teach this content, teachers should be clear about the distance between the impossibility of direct experience of students working with these phenomena and the particularities of representations in highlighting this or that aspect of interest. Although they exist, the most immediate features of Tectonic Plates are expressed by relief. The aspects that are accessible by the direct experience of the students with these sets express only part of the characteristics of these formations. The importance of this discussion in understanding the terrestrial surface from the movements realized by the interior of the Earth - Tectonic Plates - is directly related to the activities developed by the humanity with the environment, as well as the impact of these activities for her. In search of the construction of this knowledge in the basic education of Geography, the teacher can have various signs: maps, photographs and diagrams. However, each of these signs has distinct communicative potentialities, allowing the teacher to select the most adequate signs to achieve their proposed goals. In this sense, the objective of this research was consolidated in offering subsidies to the teachers to analyze the particularities of the signs commonly used in the basic education of Geography. In order to do so, this work was based on the methodology of Content Analysis, proposed by Bardin (1977) and also of the Semiotics analysis, developed by Peirce (1984), before the representations that seek to illustrate the Tectonic Plates in textbooks and that are inserted in the 6th grade of Geography of elementary school. We may consider, in relation to the analysis of the books using semiotics, that the analyzed signs: photography, map and diagram, although they refer to aspects related to the Tectonic Plates, value different aspects of a similar dynamic object and can sometimes develop in children a misunderstanding about such content / subject. In general, this research contributes to demonstrate the importance of approaching the discussions of Semiotics with the teaching of Geography, in that it allows the teacher to verify what aspect of a phenomenon a given representation contemplates. In the case of the Tectonic Plates, Semiotics allows us to understand its operation in the face of nature, through the understanding of its dynamics, enabling the student to understand the conditions that govern the location and characteristics of the geographic space